EARNINGS ABILITY AND CASH FLOW IN PREDICTING EARNINGS AND CASH FLOW IN THE FUTURE (Empirical Study on the Manufacturing Companies Listed on Indonesia Stock Exchange) - Khadirin, Khadirin; Isfaatun, SE., MM, Eliya; Septi W., SE., MM, Helly (Accounting, 2010)
In the financial statements, particularly the balance sheet and earnings are still believed to be an accurate tool for its users to reduce the risk in making economic decisions. But, to report earnings until now still there is a contradiction to the conclusions relating to the benefits generated content is the information it contains, especially the ability of earnings to predict future earnings and cash flows in the short term. Similarly, cash flow statement has been required by the IAI (Indonesian Institute of Accountants) to be reported in annual financial statements of the company. This study aimed to test the ability of earnings and cash flows in predicting earnings and future cash flows. The study is based on data reported by 40 manufacturing companies go public finances for the period 2007-2008, using linear regression statistical method. For purposes of this study, analysis was also performed using the consumer price index deflator factor (Consumer Price Index / CPI). Statistical test results show that earnings as independent variables have a closer relationship with the dependent variable earnings than cash flows as independent variables against earnings. Next to the second hypothesis is found evidence of earnings as the independent variable is not significant in relation to cash flow as the dependent variable, compared predictors of cash flows on cash flow. ii While testing the third hypothesis could be concluded that earnings have no incremental predictive ability of cash flow. Keywords: Earnings, cash flows, predictive capability.